After tragedy and triumph : essays in modern Jewish thought and the American experience - Berenbaum, Michael 1945- (Cambridge Univ. Press, 1990)
The life and times of the American Jews are seen in relation to the Holocaust and the creation of the State of Israel. He traces the Holocaust's impact on contemporary Jewish thought and on Western civilization.